Sunscreen application to the face persists beyond 2 hours in indoor workers: an open-label trial - Chutima Rungananchai (2020)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Background: The American Academy of Dermatology recommends reapplication of sunscreen every two hours for adequate sun protection when outdoor. However, the frequency of reapplication needed to achieve adequate protection in indoor workers remains unknown. Objective: To investigate the persistence of sunscreen applied once in the morning on the face of indoor workers throughout a normal 8-hour workday. Methods: This open-label trial included 20 healthy volunteers who work indoors. Volunteers applied 1 g of sunscreen (2 mg/cm2) mixed with 2% invisible blue fluorescent agent on the face in the morning. Photographs were taken by VISIA-CR booth in UV mode at 8 am and then every 2 hours thereafter until 4 pm with limited outdoor activity less than 1 hour. Six areas of the face were analyzed using digital image analysis software. The primary outcome was the total amount of sunscreen diminution during the 8-hour study period. Results: The amount of sunscreen decreased with mean peak reduction of 16.3% at 2 hours, and minimal reduction thereafter. Total sunscreen reduction was 28.2% at the end of the 8-hour day. Limitations: Small study population. Conclusion: For indoor workers who applied adequate amount of sunscreen once in the morning, reapplication of sunscreen may be unnecessary.